2022
DOI: 10.1002/wsb.1356
|View full text |Cite
|
Sign up to set email alerts
|

Resource selection of deer hunters in Georgia's Appalachian Mountains

Abstract: White-tailed deer (Odocoileus virginianus) and hunters on 2 Wildlife Management Areas (WMAs) within the Chattahoochee National Forest of northern Georgia, USA, significantly declined in number from the 1980s to 2018. Managers were interested in understanding how they could manipulate hunter distribution according to deer management goals. To understand the spatial distribution of hunting pressure and factors driving hunter resource selection, we analyzed GPS tracking data from 58 deer hunters over the 2018-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Based on the land area to hunter ratio, there was only 1 hunter for every deer's 90% UD. Furthermore, Rosenberger et al [39] found that hunting pressure was not uniform across the same study area. While hunters on the WMAs in our study area selected areas closer to deciduous forest and wildlife openings [39], the 90% UDs of female deer only averaged 17% deciduous forest and were an average distance of 553 m from a wildlife opening.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on the land area to hunter ratio, there was only 1 hunter for every deer's 90% UD. Furthermore, Rosenberger et al [39] found that hunting pressure was not uniform across the same study area. While hunters on the WMAs in our study area selected areas closer to deciduous forest and wildlife openings [39], the 90% UDs of female deer only averaged 17% deciduous forest and were an average distance of 553 m from a wildlife opening.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Rosenberger et al [39] found that hunting pressure was not uniform across the same study area. While hunters on the WMAs in our study area selected areas closer to deciduous forest and wildlife openings [39], the 90% UDs of female deer only averaged 17% deciduous forest and were an average distance of 553 m from a wildlife opening. Overall, the average relative probability of hunter selection within the 90% UDs was 27%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fish and Wildlife Service, and U.S. Department of Commerce, U.S. Census Bureau 2016). With fewer sport hunters afield (Stedman et al 2004, Rosenberger et al 2021, Rosenberger et al 2022), coupled with decreasing access for hunters on private lands (Haggerty and Travis 2006, Fontaine et al 2019), managers have fewer options to manage game populations across landownerships, including reduced decision space to lessen depredation of crops and other resources (Walter et al 2010, Johnson et al 2014). Thus, investigating factors that contribute to hunter success can help inform wildlife population management and hunting season structure (Schmidt et al 2005, Ward et al 2008).…”
mentioning
confidence: 99%